Developing E-module on the Topic of Integrated Addictive Substances with Islamic Values - Cucu Zenab Subarkah; Aflah Azifa Alhak; Sari Sari; Uus Ruswandi; Chaerul Rochman (Jurnal Tadris Kimiya, 2021)
E-module is one of the media that is considered efficient to be used as a learning media. This research describes the e-module of addictive substances integrated with Islamic values as a solution in preventing and reducing addictive substance abuse, especially among adolescents, by providing scientific knowledge related to religious knowledge. The study aims to analyze the characteristic of e-module and validation results. The e- module is designed with the Design-Based Research (DBR) method with the three steps: analysis, design, and development. Based on the results, the e-module display Islamic views and their interpretation, animated videos, questions, attitude tests, and games. The validation result indicates that the e-module is valid and feasible to be used as a learning media.